Sentidos preferenciais e mediações culturais: relevância das instituições família, trabalho e religião na recepção de narrativas jornalísticas - Winques, Kérley (2024)
This article, stemming from two doctoral theses, aims to comprehend the influence of the family, work, and religion institutions in the identification of preferential meanings—frames that readers employ to connect with a message—in the reception of journalistic narratives. Drawing from biographical fragments—memories triggered during in-depth interviews—gathered through a common life history question in both theses, the relevance of these three institutions in the daily lives of 34 participants is discussed. The results indicate that these reference communities are already identified in life stories through: a) spontaneous association; b) stimulated association; c) spontaneous dissociation; and d) stimulated dissociation. Through these analytical categories, it becomes possible to identify the constitutive foundations of cultural mediations, dimensions in which meanings originate and are shaped through media consumption.